"New" metastases are associated with a poorer prognosis than growth of pre-existing metastases in patients with metastatic breast cancer treated with chemotherapy. Issue 1 (December 2015) - Twelves, Christopher; Cortes, Javier; Kaufman, Peter; Yelle, Louise; Awada, Ahmad; Binder, Terri; Olivo, Martin; Song, James; O'Shaughnessy, Joyce; Jove, Maria; Perez, Edith
Abstract Introduction Progression-free survival (PFS) and overall survival (OS) endpoints often only weakly correlate. This analysis investigates how different progression events impact on OS, using data from two phase 3 studies with eribulin in women with advanced/metastatic breast cancer (MBC). Methods In Study 301, 1102 women with ≤2 prior chemotherapies for advanced/MBC were randomized to eribulin mesylate (1.4 mg/m2 on days 1 and 8 every 21 days) or capecitabine (1.25 g/m2 twice daily on days 1–14 every 21 days). Study 305/EMBRACE enrolled 762 patients following two to five prior chemotherapies for advanced/MBC, randomized to eribulin (as above) or treatment of physician's choice. We analyzed OS and PFS post hoc for patients whose disease progressed due to development of "new" metastases, growth of pre-existing lesions, and patients with no reported disease progression. Results In both clinical studies, development of new metastases was associated with an increased risk of death (p  < 0.0001). The time to development of new metastasis or death was significantly longer with eribulin than the comparator in Study 305 (p  = 0.0017), but not in Study 301 (p  = 0.46). Significantly longer OS was observed in the eribulin compared with the comparator arm for the new metastases subgroup in Study 301 (p  = 0.008), but not in Study 305 (p  = 0.16), compared with other progression subgroups. Conclusions Patients with MBC progressing with new metastases have a worse prognosis than those whose disease progresses due to growth of existing lesions or patients with no reported disease progression. These findings have potentially important implications for the interpretation of clinical study data and clinical practice. Trial registration ClinicalTrials.gov registration IDs: Study 301:NCT00337103 ; Study 305:NCT00388726 .